Food Safety Risk in Germany From Mislabeled Imported Fish: Ciguatera Outbreak Trace-Back, Toxin Elucidation, and Public Health Implications - Loeffler, Christopher R.; Spielmeyer, Astrid; Friedemann, Miriam; Kapp, Katrin; Schwank, Ulrich; Kappenstein, Oliver; Bodi, Dorina (Frontiers in Marine Science, 2022)
Ciguatera poisoning (CP) is a prevalent food related health risk, caused by the consumption of seafood contaminated with ciguatoxins (CTXs). Seafood is the most traded food commodity worldwide, and since 2012, imported snapper fish (Lutjanidae) were the leading cause of CP in Germany. Following a Germany wide CP outbreak in 2017, a product trace-back investigation was conducted for imported fish labeled as “Red Snapper” (Lutjanus malabaricus). Forty-five fish muscle-tissue portions from the implicated batch and two meal remnants were analyzed for CTXs. All samples were positive for “CTX-like toxicity” containing a range of 0.23–11.4 ng CTX3C equivalents per gram of wet tissue, determined by an in vitro cell assay [N2a-3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT)]. Liquid chromatography with tandem mass spectrometry (LC-MS/MS) chromatograms revealed the (potential) presence of several marine biotoxins of the class CTX in all batch samples. All samples exceeded current multi-national product legal requirements and recommended guidelines for CTXs. DNA barcoding confirmed the fish sold was mislabeled and was identified as L. bohar, a species frequently involved in CP. Consequently, the mislabeled food and contaminants risk focuses attention on the importance of correct food labeling. Processes for food authentication and CTX contaminant analysis exist and can be used to potentially prevent, stop, and remove foods from commerce for further evaluation to ensure consumer safety. This study further demonstrates their necessity.